Increasing the Volume of Agro-Industrial Production to Ensure Food Security and Increase the Export Potential of the Russian Agricultural Sector - Ushachev , Ivan G.; Maslova , Vlada V.; Andrey V. Kolesnikov , Andrey V. Kolesnikov (Economy of Regions, 2022)
Currently, the Russian